Refractory Status Epilepticus : Diagnosis and Treatment - Wang, Xuefeng; Li, Shichuo (Springer Singapore : Imprint: Springer, 2017)
This book aims to offer the accumulated fertile experience of treating drug-resistant epileptic patients collected over the past few decades, focusing on aspects of neurology, neurosurgery, emergency care, critical care medicine and basic medical research. Refractory status epilepticus is one of the most common severe and acute diseases in neurology and neurocritical care; it is also the main cause of death in epileptic patients. In the context of prevention and treatment processes, it is not only necessary to terminate epileptic seizures, but to also address the disruption of the patient's internal environment and provide critical life support. Effective treatment calls for multi-disciplinary support from neurology, neurosurgery, emergency care, critical care medicine, and other fields. Further, since the clinical features of epileptic seizure are not specific, it is necessary to differentiate it from other diseases that produce convulsions, disorders of consciousness, syncope, mental and behavioral disorders, myoclonus, etc., to avoid misdiagnosis. In this book, it comprehensively and systematically describes the basic knowledge as well as prevention and treatment tips, providing an invaluable reference resource for medical students and professionals in neurology, neurosurgery, emergency care and critical care medicine.
Keywords: Medicine.; Neurology.; elektronické knihy; electronic books